Sensitivity Analysis and Comparison between 25 kW Parabolic Dish System - Mohd Ruddin Ab Ghani; Liaw Geok Pheng; Chin Kim Gan; Tole Sutikno (Universitas Ahmad Dahlan, 2016)
Dish-Stirling concentrating solar power systems is an efficient and reliable source of renewable energy. In this paper, the proposed model showed the idea of Parabolic Dish (PD) systems with control system model which vary the amount of working gas in the Stirling engine. The control systems were designed using Matlab /Simulink 2012a. Based on the developed linearized model, an improved temperature controller with transient droop characteristic and Mean Pressure Control (MPC) has been proposed. This temperature controller was effective in reducing the temperature and improving performance of the PD system. The overall performance of the system improved more than 78% in output power and energy. Besides, the system improved in term of sensitivity compared with the PD system without compensated. In addition, thermal losses decreased to 97.6% which is directly have significant improvement for the output efficiency to the system. The analysis shows that the PD system is feasible in term of technical but not economically feasible in the Malaysia environment.